2015
DOI: 10.1002/anie.201504171
|View full text |Cite
|
Sign up to set email alerts
|

A Neutral Silicon/Phosphorus Frustrated Lewis Pair

Abstract: Frustrated Lewis pairs (FLPs) have a great potential for activation of small molecules. Most known FLP systems are based on boron or aluminum atoms as acid functions, few on zinc, and only two on boron-isoelectronic silicenium cation systems. The first FLP system based on a neutral silane, (C2F5)3SiCH2P(tBu)2 (1), was prepared from (C2F5)3SiCl with C2F5 groups of very high electronegativity and LiCH2P(tBu)2. 1 is capable of cleaving hydrogen, and adds CO2 and SO2. Hydrogen splitting was confirmed by H/D scramb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
106
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 44 publications
6
106
0
5
Order By: Relevance
“…We have recently reported the synthesis of the first neutral silicon/phosphorus FLP, (C 2 F 5 ) 3 SiCH 2 P( t Bu) 2 ( 1 ) . Its activity in H 2 splitting, and addition of CO 2 and SO 2 is due to the highly electron‐withdrawing pentafluoroethyl groups, which turn the silane function into a strong Lewis acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported the synthesis of the first neutral silicon/phosphorus FLP, (C 2 F 5 ) 3 SiCH 2 P( t Bu) 2 ( 1 ) . Its activity in H 2 splitting, and addition of CO 2 and SO 2 is due to the highly electron‐withdrawing pentafluoroethyl groups, which turn the silane function into a strong Lewis acid.…”
Section: Methodsmentioning
confidence: 99%
“…With their chlorogermane (C 2 F 5 ) 3 GeCl we were now able to prepare a neutral germanium‐containing FLP, (C 2 F 5 ) 3 SiCH 2 P( t Bu) 2 ( 2 ), by reacting it in a nucleophilic substitution reaction with the lithiated phosphane LiCH 2 P( t Bu) 2 (Scheme ) . This enables us to explore its chemistry in comparison to the silicon analogue 1 …”
Section: Methodsmentioning
confidence: 99%
“…There are diverse types of FLPs, particularly, employed to fix CO 2 , such as, intermolecular P/B‐FLP, for example, t Bu 3 P/B(C 6 F 5 ) 3 pair (compound a ), intramolecular methylene‐ or ethylene‐bridged FLPs t Bu 2 P(CH 2 )Si(C 2 F 5 ) 3 (compound b ) and Mes 2 P(CH 2 ) 2 B(C 6 F 5 ) 2 (compound c ), which are the typical germinal ( b ) and vicinal ( c – d ) systems, respectively. In 2012, Stephan and co‐workers investigated that amidophosphorane ( d ), a P/N‐based FLP, can achieve CO 2 capture readily at mild conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently demonstrated that guanidine 1,5,7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) and the relative derivatives featuring a boryl or silylium site, TBD–BR 2 and [TBD–SiR 2 ] + , respectively, strongly bind to CO 2 and other heterocumulenes to yield stable adducts (Schemes and ). Although SO 2 and CO 2 molecules have distinct chemical properties, they are readily trapped by FLPs to form similar adducts . The structural characteristics and chemical behaviors of the FLP–ZO 2 (Z=C, S) adducts have however never been compared and discussed.…”
Section: Introductionmentioning
confidence: 99%